2018
DOI: 10.1002/jso.25034
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized lymph node transfer for treatment of extremity lymphedema: An overview of current controversies regarding donor sites, recipient sites and outcomes

Abstract: As lymphatic microsurgery has become more common, vascularized lymph node transfer ascended to the forefront in many centers for the surgical management of advanced stages of lymphedema showing substantial clinical improvement. However, no consensus has been reached among experts regarding many details of the procedures, including patient selection criteria, type of treatment, donor, and recipient sites and postoperative evaluation of the outcome. Here, we will review these issues and provide the current resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 66 publications
0
40
0
2
Order By: Relevance
“…VLN transfer is a promising technique for treating moderate-to-advanced stage lymphedema, and it has the ability to lower the clinical grade, attenuate limb circumference, reduce the incidence of cellulitis and improve the quality of life in patients (117). However, it requires a strict observation Can only be used in the moderate-to-advanced stage of LE; reduces limb volume or circumference and the incidence of cellulitis; improves quality of life; donor-site lymph edema is a potential complication Liposuction Removes excess adipose tissue; improves lymph flow; increases blood flow to the skin; reduces the incidence of erysipelas and cellulitis LE, lymphedema. of the donor site because donor site lymphedema is the most serious complication after this surgery (117). Patient selection and scrupulous assessment of donor and recipient sites prior to VLN transplantation are key factors for surgical success.…”
Section: Treatmentmentioning
confidence: 99%
“…VLN transfer is a promising technique for treating moderate-to-advanced stage lymphedema, and it has the ability to lower the clinical grade, attenuate limb circumference, reduce the incidence of cellulitis and improve the quality of life in patients (117). However, it requires a strict observation Can only be used in the moderate-to-advanced stage of LE; reduces limb volume or circumference and the incidence of cellulitis; improves quality of life; donor-site lymph edema is a potential complication Liposuction Removes excess adipose tissue; improves lymph flow; increases blood flow to the skin; reduces the incidence of erysipelas and cellulitis LE, lymphedema. of the donor site because donor site lymphedema is the most serious complication after this surgery (117). Patient selection and scrupulous assessment of donor and recipient sites prior to VLN transplantation are key factors for surgical success.…”
Section: Treatmentmentioning
confidence: 99%
“…However, although numerous investigators have published outcomes following lymphovenous bypass [6][7][8][9], vascularized lymph node transplantation [2,3,[10][11][12][13][14], and liposuction [5,15], a detailed discussion of the assessment of prospective surgical candidates has not been reported. As a result, there are currently many preoperative assessment protocols complicating comparison of outcomes between centers [16][17][18][19][20][21][22]. In addition, the rationale, utility, and comparative efficacy of preoperative tests for lymphedema has not been formally reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Common donor sites for vascularized lymph node transfer include the inguinal (Becker et al, ; Clodius, Smith, Bruna, & Serafin, ; Gharb et al, ; Lin et al, ), axillary (Dayan, Dayan, & Smith, ), submental (Cheng et al, ; Patel et al, ), supraclavicular (Althubaiti, Crosby, & Chang, ; Steinbacher et al, ), and lateral thoracic (Batista, Germain, Faria, & Becker, ; Becker et al, ) regions. However, donor site morbidity remains a concern, including iatrogenic lymphedema, lymphorrhea, nerve injury, and conspicuous scar (Ciudad et al, ; Pappalardo, Patel, & Cheng, ; Patel et al, ; Sulo et al, ; Viitanen, Maki, Seppanen, Suominen, & Saaristo, ). In the search for a better source of lymph node transfer, intraabdominal donor sites such as the jejunal mesentery (Coriddi, Skoracki, & Eiferman, ) and omentum (Agko, Ciudad, & Chen, ; Ciudad et al, ) have recently been reported to pose a lower risk for iatrogenic lymphedema (Agko et al, ).…”
Section: Introductionmentioning
confidence: 99%